Comparative analysis of species composition and quantitative analysis of udder microflora in cows with subclinical and clinical mastitis - N. N. Avduevskaya; A. V. Kapustin; A. V. Gorbatov; E. V. Ivanov (Ветеринария сегодня)
Due to the great relevance of the problem of mastitis in cows, the diversity of udder microflora in the affected animals, as well as to develop therapeutic and preventive measures on farms, studies were conducted to identify similarities and differences in the species composition of microorganisms in animals with subclinical and clinical breast inflammation, their proportion, to establish the correlation between the secreted microflora and the type of mastitis, as well as to study and compare the enzymatic properties of Staphylococcus aureus isolated from animals with clinical and subclinical mastitis. It was found that on all the studied farms the number of cows and heifers with subclinical mastitis exceeded the number of animals with clinical udder inflammation. As a result of microbiological studies of 182 mammary gland secretion samples collected from cows with subclinical and clinical mastitis from 13 agricultural establishments of the Vologda, Yaroslavl and Kostroma regions, 70 cultures of pathogenic and opportunistic microflora were isolated. It was demonstrated that, in case of subclinical mastitis, the following cultures were most often isolated from milk: Staphylococcus aureus (17.9% of cases), pathogenic Streptococcus (9.8% of cases), of which the proportion of Streptococcus agalactiae and Streptococcus dysgalactiae was 6.5 and 3.3%, respectively. Opportunistic Staphylococcus (6.5%) and Enterobacteria (6.5%) were isolated in equal proportions. In case of cows with clinical mastitis, Staphylococcus aureus was isolated in 16.9% of cases, pathogenic Streptococcus – in 10.2% of cases, of which the proportion of Streptococcus agalactiae and Streptococcus dysgalactiae was 6.8 and 3.4%, respectively. Opportunistic Staphylococcus and Enterobacteria were found in equal amounts – 3.4% of cases each. No growth of Mycoplasma on special nutrient media was registered in both cases. It was established that similar pathogenic and opportunistic microorganisms are isolated from animals with subclinical and clinical mastitis. The main causative agent is Staphylococcus aureus, the incidence of which in case of latent mastitis is slightly higher (by 1.0%). It is followed by Streptococcus agalactiae and Streptococcus dysgalactiae, which are detected more often in case of clinical udder inflammation – by 0.2% on average. The frequency of isolation of opportunistic Staphylococcus is 1.9 times higher in case of subclinical mastitis. It is worth noting that with clinical udder inflammation, enterobacteria were detected only at one of the thirteen studied agricultural establishments.